Fostering Human Dignity Through Human Resource Development: Ethical Practices, Cultural Variations, and Emerging Trends - -, Nanik Wahyuningtiyas; Cindy Pramita; Agung Winarno; Heri Pratikto (Social Science Studies, 2024)
Research Aims: This study aims to examine the integration of human dignity within Human Resource Development (HRD) practices, assessing its impact on organizational culture, employee engagement, and ethical workplace dynamics. It seeks to explore how dignity-centered HRD can enhance both personal and organizational growth, focusing on the psychological and cultural dimensions of HRD strategies. Design/methodology/approach: Utilizing a qualitative methodology, the research will combine theoretical analyses with case studies from multinational companies. It will involve a comprehensive review of philosophical and contemporary HRD frameworks that prioritize human dignity, alongside empirical data collected through interviews and surveys with HR professionals and employees. Research Findings: The study is expected to reveal that embedding dignity in HRD practices contributes significantly to workplace ethics, productivity, and individual well-being. It will show that respectful treatment increases employee motivation and engagement, reducing turnover and fostering a more inclusive organizational culture. Theoretical Contribution/Originality: This research contributes to HRD literature by providing a nuanced understanding of how dignity intersects with HR practices to foster ethical decision-making and personal development. It offers a unique blend of philosophical insights and practical applications, highlighting the role of dignity in achieving sustainable organizational success and employee satisfaction.